Legal Analysis of Implicationsconstitutional Court Decision No.60/PUU-XXII/2024 on Simultaneous Regional Head Elections and Democracy - Muhammad Ihza Yuris Setiawan; Labib Muttaqin (Proceeding International Conference Restructuring and Transforming Law, 2025)
Constitutional Court Decision Number 60/PUU-XXII/2024 which has urgency for the implementation of the 2024 Pilkada. This study aims to determine the implications of the Constitutional Court Decision on regional head elections and democracy and how judges consider in deciding the decision. The approach used is the Statute Approach which conducts a review of laws and regulations related to the legal issues being studied. This type of research is juridical-normative research, juridical research that examines legal perspectives based on statutory regulations, and normative research to find legal regulations, and legal doctrines that are useful for answering existing issues. The data collection process is carried out by collecting primary legal materials, secondary legal materials, and non-legal materials through library research or searching for information on the internet. The data obtained is then collected to ensure its validity. The results of the study show that based on the considerations of the Panel of Judges which states that Article 40 paragraph (1) and paragraph (3) of Law No. 10 of 2016 is unconstitutional against the 1945 Constitution, then the results of the Constitutional Court decision N0.60 / PUU-XXII / 2024 emerged, the results of which changed the nomination threshold depending on the permanent election list in each region. This decision opens the door for parties that do not have enough votes in the DPRD to be able to nominate their candidates as regional heads as long as they meet the requirements, and equalizes the rights and requirements for candidates who are in political parties and individual candidates to be able to nominate themselves as regional heads.